HUBUNGAN STATUS GIZI DENGAN HASIL BELAJAR SISWA KELAS V PUTRASD 039 AIR TERBIT KEC. TAPUNG KAB. KAMPAR - Ayu Herizon; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation of male students class V of SDN 039 Air Terbit in Tapung district of Kampar. Researcher found the quality of learning outcomes of sport education still low. Evident from learning outcomes still below average or below standars that class rise to minimal completeness criteria 7,5, so many student do remedial. The purpose of this research is to see correlation of the nutritional status with learning outcomes male students class V of SDN 039 Air Terbit in Tapung District of Kampar . Population in this research is all male students in class V amount 18 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 18 people. Research instrument used were the high and weight test and learning outcomes test from raport outcomes. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : that is result obtained from 18 male students in class V of SDN 039 Air Terbit in Tapung District of Kampar. Shows that there is correlation of the nutritional status with learning outcomes, which shows rhitung (0,065) < rtabel (0,482).Key word : Nutritional Status, Learning Outcomes